Make ink : a forager's guide to natural inkmaking - Logan, Jason; Kolyn, Lauren; Ondaatje, Michael, 1943- (New York : Abrams, 2018)
The Toronto Ink Company was founded in 2014 by designer and artist Jason Logan as a citizen science experiment to make eco-friendly, urban ink from street-harvested pigments. In Make Ink, Logan delves into the history of inkmaking and the science of distilling pigment from the natural world. Readers will learn how to forage for materials such as soot, rust, cigarette butts, peach pits, and black walnut, then how to mix, test, and transform these ingredients into rich, vibrant inks that are sensitive to both place and environment. Organized by color, and featuring lovely minimalist photography throughout, Make Ink combines science, art, and craft to instill the basics of ink making and demonstrate the beauty and necessity of engaging with one of mankind's oldest tools of communication.
Foreword / by Michael Ondaatje -- Introduction -- Find ink. On foraging ; A forager's checklist ; On foraging in winter -- Make ink. What is ink and how is it made? ; Natural ink: a basic recipe ; The ground rules of natural inkmaking ; Colors and recipes -- Test ink. Testing ink on paper ; On collaboration with artists -- Conversation with Michael Ondaatje -- A timeline of ink.
Includes artwork by Marta Abbott ; Margaret Atwood ; Ani Castillo ; Marcel Dzama ; Dave Eggers ; Hugo Guinness ; Heidi Gustafson ; Tucker Nichols ; Kayo Nomura ; Hiroaki Ooka ; Jason Polan ; Edel Rodriguez ; Seth ; Leanne Shapton ; Tamara Shopsin ; Gary Taxali
Includes bibliographical references (page 190).
Keywords: Henseler, Thomas; Dyes and dyeing; Dyes and dyeing; Dyes and dyeing; Forage plants; Forage plants; Forage plants; Ink painting; Ink painting; Ink painting; Ink; Ink; Ink; Naturfarbstoff; Illustrated works; Nonfiction